Comparison between soil maps obtained by spectral remote sensing and conventional method - Demattê, José Alexandre M.; Genú, Aline Marques; Fiorio, Peterson Ricardo; Ortiz, Jonas Luís; Mazza, Jairo Antônio; Leonardo, Hudson Carlos Lissoni (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to compare the use of the spectral remote sensing for producing soil maps to the conventional method. Using a planialtimetric base map, thirty sampling points were demarcated in the studied area. The samples were collected at 0–20, 40–60 and 80–100 cm depth in each point, all georreferenced, with the total of ninety samples in which the chemical, physical and radiometric analyses were performed. The radiometric data were obtained in laboratory using the spectroradiometer IRIS, in the range of 400–2,500 nm. Using the analyses and interpretation of both the spectral and the planialtimetric data, a detailed spectral soil map was obtained. For the same area, a conventional detailed map was also obtained. Four soil classes were identified in both maps. The produced maps presented good correlation, demonstrating that spectral data can be used as tool in soil survey. The use of spectral remote sensing, planialtimetric data and field work allows the obtention of a detailed soil map.